Assessment of Public Special Education Teachers Training Needs on Evidence-Based Practice for Students with Autism Spectrum Disorders in Spain - Aitor Larraceleta; Luis Castejón; María-Teresa Ig; José Carlos Núñez (MDPI AG, 2022)
Over decades, the concern for the quality of psychoeducational practices for students with autism spectrum disorders has led to study to what extent are evidence-based educational methods disseminated among teachers. The purpose of this cross-sectional study, taking as reference Hsiao and Sorensen's previous research, was to identify through a survey to what extent social-communication evidence-based practices for these students were provided in teacher education and in-service training programs, in a sample of 108 special education teachers from Spain, and to compare these results with Hsiao and Sorensen's. Overall, more than 70% of the teachers reported that evidence-based practices in their teacher education programs (87.6%) and in-service training programs (73.6%) were never taught or mentioned incidentally. Finally, a higher percentage of addressing on each practice (i.e., mentioned and discussed or mentioned and taught through direct instruction) is shown in the sample of American teachers compared to the Spaniards, in both training paths.